KARAKTERISTIK PAPAN PARTIKEL DARI BATANG PANDAN MENGKUANG (Pandanus atrocarpus Griff) BERDASARKAN UKURAN PARTIKEL DAN KONSENTRASI UREAFORMALDEHIDA - Maulana, Daeng; Dirhamsyah, M; Setyawati, Dina (Universitas Tanjungpura, 2015)
This research is aimed to know the effect size of the particle and concentration adhesives of urea formaldehyde to physical and mechanical properties particle board.Particle board made from the stem of Pandan Mengkuang (Pandanus atrocarpus Griff) from Ambawang Subdistrict, the Regency of Kubu Raya. The size of the particle, which consists of the coarse particle size 4 - 6 meshes, the soft particle size 8 - 10 meshes. The level of urea formaldehyde used the were 10%, 12% and 14% from the basic material mass.Particle board is made with size 30 cm x 30 cm x 1 cm with target density of 0,6 g/cm3at a specificpressure of25 kg/cm2 and temperature of 150º C for 10 minutes. Evaluation of the physical properties and mechanical properties was conducted according to JIS A 5908-2003.The results of this research showed the average value based the density is around 0,58 g/cm3 – 0,66 g/cm3, the moisture content is around 7,79% - 9,72%, thickness swelling is around14,72% - 21,59%, water absorption is around 74,40% - 99,65%,modulus of elasticity is around 5122,05 kg/cm2 – 10995,76 kg/cm2, modulus of repture is around 109,22 kg/cm2 – 194,15 kg/cm2,the internal bonding strengthis around 2,74 kg/cm2 – 3,59 kg/cm2, and the screws holding strength is around 52,06 kg – 77,09 kg. The best treatment for the physical and mechanical of particle board made from Pandan Mengkuang (Pandanus atrocarpus Griff) stem is the size of the coarse particle and urea formaldehyde concentration 14%. Key words : Pandan mengkuang, particleboard,urea formaldehyde